AI Socialization in Creating Teaching Materials for Elementary School Teachers in Bukittinggi City West Sumatra - Liza Efriyanti, Liza Efriyanti; Sarwo Derta; Firdaus Annas (Salus Publica: Journal of Community Service, 2024)
The use of Artificial Intelligence (AI) in education offers innovative solutions to improve the quality of learning, especially in creating teaching materials. However, in Bukittinggi City, West Sumatra, many elementary school teachers have not yet utilized this technology due to limited knowledge and skills. Therefore, this community service activity aims to socialize and train elementary school teachers in utilizing AI to create interactive and effective teaching materials. The implementation method of this activity includes socialization of AI theory, practical training on the use of AI applications, group discussions, and direct practice in creating AI-based teaching materials. The results of this activity show an increase in teachers' understanding and skills in using AI. As many as 75% of teachers are able to create more varied and efficient teaching materials by utilizing AI technology. However, several obstacles were found, such as limited technological infrastructure in schools. This socialization activity succeeded in improving teachers' ability to utilize AI, but limited technological infrastructure is a major challenge. The evaluation showed that most teachers needed further training to deepen their understanding of AI technology. In the future, there needs to be increased access to technology and ongoing training to ensure the sustainability of AI utilization in elementary education in Bukittinggi